Personal assistants in England and the factors associated with absenteeism - Roland, Daniel; Allan, Stephen; Chambers, Eleni; Smith, Debs; Gousia, Katerina (Frontiers in Public Health, 2022)
Personal assistants (PAs) have become an increasingly important element of long-term care (LTC) in England since the introduction of Direct Payments in 1996 and the Care Act 2014 legislation. The PAs, who are directly employed by social care users, can perform a number of support tasks including vital assistance in activities of daily living (ADL). Internationally these roles would be classed as domestic care work, including the employment of migrant care workers, e.g. in Germany and Austria. High turnover rates and work absenteeism in this market can cause disruption of these important daily activities, causing LTC users to potentially suffer neglect and poorer quality of life. Although there is research on turnover and absenteeism in nursing workforce in hospitals and LTC workers in nursing homes, little attention has been given to reasons for turnover of PAs and even less for absenteeism, which often precedes turnover, in a workforce of over 100,000 people in England. This research aims to fill this gap in knowledge by analysing the reasons behind the absenteeism of PAs using quantitative methods. We used survey data of PAs in England, exploring the factors associated to one form of absenteeism – sick leave from work. After controlling for a number of factors ranging from job characteristics such as number of hours worked and type of contract, socio-economic characteristics from the PA and their employer, and supply and demand factors at local government region, the findings suggest a number of factors that significantly influenced sick leave, including distances travelled to work and number of PAs employed. Following the analysis, two people with life experience of LTC discuss the findings of the study and how they compare to their experiences of the market for PAs, providing a unique perspective from the people who could benefit the most from improving PA retention and reducing absenteeism.